2010
DOI: 10.1007/s11079-009-9161-5
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Shocks and The Sectoral Composition of Output

Abstract: Government spending shocks, Tradables, Nontradables, European Monetary Union, Panel VAR, E24, E62,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 38 publications
6
27
0
Order By: Relevance
“…3 While the Ramey-Shapiro narrative approach suggests that military shocks, which are heavily concentrated in the manufacturing sector, are intensive in traded goods, our study reveals that government spending shocks, identified on the basis of Blanchard-Perotti assumption, lead to a sharp increase in non traded output relative to traded output. This finding is in line with estimates documented by Monacelli and Perotti [2008] and Benetrix and Lane [2010], which show that an increase in government spending disproportionately benefits the non traded sector. In contrast to the authors who restrict their attention to sectoral output effects, we highlight the changes in sectoral shares in labor and real GDP.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…3 While the Ramey-Shapiro narrative approach suggests that military shocks, which are heavily concentrated in the manufacturing sector, are intensive in traded goods, our study reveals that government spending shocks, identified on the basis of Blanchard-Perotti assumption, lead to a sharp increase in non traded output relative to traded output. This finding is in line with estimates documented by Monacelli and Perotti [2008] and Benetrix and Lane [2010], which show that an increase in government spending disproportionately benefits the non traded sector. In contrast to the authors who restrict their attention to sectoral output effects, we highlight the changes in sectoral shares in labor and real GDP.…”
Section: Introductionsupporting
confidence: 92%
“…14 This definition corresponds to that implicitly adopted by Monacelli and Perotti [2008] and Benetrix and Lane [2010]. 15 To derive the second definition, we use the fact thatŶ (t) = dG(t)/Y (by keeping private demand fixed) along with (4) and ν Y,jŶ j (t) = ω G j (dG(t)/Y ).…”
Section: Var Specificationmentioning
confidence: 99%
“…6 The substantial increase in non traded output following a rise in government spending is in line with the evidence documented by Benetrix and Lane [2010] who find that the relative size of the non traded sector increases disproportionately after a temporary fiscal shock. 7 The unit cost function is a weighted average of the wage rate and the rental rate of capital.…”
Section: Introductionsupporting
confidence: 70%
“…There are also a number of empirical studies that find that the EMU led to an increase in expansionary and electorallymotivated fiscal policy (Buti and Van Den Noord, 2004;Efthyvoulou, 2012;Mink and De Haan, 2006), as well as a rise in overly optimistic budget deficit forecasts aimed at misleading electorates, especially in the run up to elections (Brück and Stephan, 2006). In turn, there is also robust evidence that fiscal policy expansions in EMU countries result in a deterioration in the trade balance (Beetsma and Giuliodori, 2010;Bénétrix and Lane, 2010).…”
Section: Literature Review: the Emu And Current Account Balancesmentioning
confidence: 99%